Evaluation of structural-functional changes of the left ventricular myocardium in patients with arterial hypertension and obesity by the level of irisin - O. V. Shaparenko; P. H. Kravchun; P. P. Kravchun; O. I. Kadykova; H. V. Lisova (Zaporožskij Medicinskij Žurnal)
The aim was to evaluate the structural and functional changes of the left ventricular myocardium according to the data of echocardiography in patients with arterial hypertension combined with obesity by the level of irisin.